Mix Method Analysis of Factors Affecting Implementation of Antenatal Care (ANC) in Pregnant Women in the Work Area of the Medan Deli Health Center, Medan Deli District, Medan - Elya Rosa; Razia Begum Suroyo; Aida Fitria (Newinera Publisher, 2021)
workers which includes physical and mental health to get mothers and babies who are healthy during pregnancy, childbirth and postpartum. Data from the Medan Deli Health Center shows that in 2019 the K1 coverage is only (87%) and K4 only (66%), while the target of K1 and K4 coverage is 100% respectively. Many factors are thought to be the cause of not achieving coverage of antenatal care (ANC) implementation. The purpose of this study was to analyze the factors that influence the implementation of ANC in pregnant women. This type of research is a mix method with quantitative and qualitative approaches. The study population was 195 people, with the Slovin formula taken a sample of 66 people. Quantitative analysis was univariate, bivariate using chi-square and multivariate using multiple logistic regression at the 95% confidence level ( = 0.05). The qualitative analysis was analyzed by means of reduction, data display and verification. The results showed the variables that influenced the implementation of antenatal care (ANC) in pregnant women in the work area of ​​the Medan Deli Public Health Center in 2020, namely knowledge p = 0.032, attitude p = 0.018, parity p = 0.008, health services p = 0.016, husband support p = 0.026 and support for health workers p = 0.041. The unrelated variable was job status p = 0.269. The most dominant variable was the health service variable which had a value of Exp (B) = 12.048, meaning that respondents who received health services had 12 times the chance of implementing antenatal care compared to respondents who did not get health services. The conclusion of this research is that the implementation of antenatal care in pregnant women is influenced by knowledge, attitudes, parity, health services, husband support and support from health workers. It is hoped that health workers, especially midwives, will provide good IEC about the implementation of antenatal care to every pregnant woman and carry out more frequent home visit activities and provide advice to the puskesmas to re-attach the standby husband and cooperate with local regional leaders